2006
DOI: 10.1111/j.1574-6941.1997.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Conidial trap formation of nematode-trapping fungi in soil and soil extracts

Abstract: Conidial traps (CT) in nematode‐trapping fungi are trapping structures formed directly on germination of conidia, without an intermediate hyphal phase. Most of the nine fungi tested were able to form CT on water agar surfaces in the vicinity of soil, but the ability varied between species. Generally, the ability to form CT was greatest in Arthrobotrys dactyloides and Monacrosporium gephyropagum followed by Arthrobotrys superba and Arthrobotrys oligospora. The mechanism behind CT formation was further studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…This result indicates competition for nutrients by microorganisms as being one of the reasons for conidia germinating directly into traps, thus overcoming fungistatic conditions in soil. Furthermore, rhizosphere soil was more efficient than root-free soil (Persmark & Nordbring-Hertz, 1997). It remains to be shown whether conidial traps develop in the vicinity of living roots.…”
Section: Diversity Of Trapping Structures In Arthrobotrysmentioning
confidence: 94%
See 2 more Smart Citations
“…This result indicates competition for nutrients by microorganisms as being one of the reasons for conidia germinating directly into traps, thus overcoming fungistatic conditions in soil. Furthermore, rhizosphere soil was more efficient than root-free soil (Persmark & Nordbring-Hertz, 1997). It remains to be shown whether conidial traps develop in the vicinity of living roots.…”
Section: Diversity Of Trapping Structures In Arthrobotrysmentioning
confidence: 94%
“…Alternatively, traps may be formed directly upon germination without an intermediate hyphal phase to form so-called conidial traps (CTs). These structures were found in natural environments such as cow dung (Dackman & Nordbring-Hertz, 1992) and rhizosphere soil (Persmark & Nordbring-Hertz, 1997). In these environments CTs were detected not only in A. oligospora but also in several other nematode-trapping fungi (Barron, 1977;Dowe, 1987;Persmark & Nordbring-Hertz, 1997).…”
Section: Diversity Of Trapping Structures In Arthrobotrysmentioning
confidence: 95%
See 1 more Smart Citation
“…Traps are usually produced from hyphae but can also be produced by germinating conidia, especially in the case of fungi that produce constricting rings (Persmark and Nordbring-Hertz, 1997). The production of traps by germinating conidia presumably minimizes the resources and time required by the fungus to begin to compete for nitrogen (Dackman and Nordbring-Hertz, 1992).…”
Section: Morphogenesis Of Constricting Ringsmentioning
confidence: 99%
“…The nematodetrapping fungi can be induced to form traps by substances such as sterile filtrate of nematode cultures, human blood serum, extracts from earthworms, CO 2 , cellophane, small peptides, lectins, cow feces, soil, and soil extracts [4,[9][10][11][12][13][14]. Nordbring-Hertz [15] showed that the direct contact of living nematodes with hyphae was very effective at inducing traps and was more effective than peptides.…”
Section: Introductionmentioning
confidence: 99%